Arahan Strategi Pengembangan Kawasan Pelabuhan Kayu Bangkoa yang Ideal Berdasarkan Kriteria Transit Oriented Development (TOD) - Indah Rukmana; Ananto Yudoyono; Arifuddin Akil (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2019)
Bangkoa Port is not yet ideal as a TOD center, especially for commuters around the city which are the biggest contributor to transportation activities within the scope of Maminasata. This study aims to identify the criteria for implementing Transit Oriented Development (TOD) and determine the direction of the Bangkoa Port Development Area.. The analysis was carried out by means of a qualitative descriptive analysis technique for existing conditions and a comparative analysis comparing existing conditions to the ideal area, and using SWOT analysis to determine the direction of the development strategy and AHP analysis to determine the priority hierarchy of the concept of TOD treatment in the Timber Port Area Bangkoa. The results of this study indicate that 1) Based on the analysis results, there are 3 aspects that are in accordance with the TOD technical criteria, namely the character of development, the intensity of space use, mix and diversity of space use. There are 3 aspects that are not appropriate, namely the regional transit system, the parking system, the pedestrian way, and public spaces; 2) Kayu Bangkoa port Area in quadrant I shows a growth strategy (increasing growth through designing integrated monorail route plans and stations with space utilization, optimizing long-term transit modes connected by short-term transit modes, planning monorail stations connected to service centers.